Stabilization of Solar-Wind Hybrid Power System by Using SMES - S.M. Mohiuddin; M.R.I. Sheikh (Institute of Advanced Engineering and Science, 2014)
The depleting fossil fuel reserves and increasing concern towards global warming created the need to surge for the renewable energy sources. Wind and solar power generation are two of the most promising renewable power generation technologies. This paper deals with the simulation of a Solar-Photovoltaic and Wind hybrid power generation system equipped with Superconducting Magnetic Energy Storage (SMES) in MATLAB/SIMULINK environment. The Solar-Photovoltaic Module and Permanent Magnet Synchronous Generator (PMSG) based wind turbine is simulated separately. Then they are connected to a dc bus. Since the intermittent nature of Solar and Wind makes the system unreliable, so an energy storage system SMES is introduced to reduce output fluctuations. Varying wind speed and solar irradiance value are taken as the input parameters. The simulation results show that a system with SMES is more reliable than a system without SMES.DOI:http://dx.doi.org/10.11591/ijece.v4i3.6039